Pilot-scale demonstration of advanced adiabatic compressed air energy storage, Part 2: Tests with combined sensible/latent thermal-energy storage. (June 2018) - Becattini, V.; Geissbühler, L.; Zanganeh, G.; Haselbacher, A.; Steinfeld, A.
Highlights: Pilot-scale demonstration of advanced adiabatic compressed air energy storage. Compressed air stored in mostly unlined rock cavern. Thermal energy stored in combined sensible/latent storage. Latent storage based on eutectic AlCuSi metal alloy. Air temperatures during charging of up to 550 °C. Abstract: Experimental and numerical results from the world's first pilot-scale advanced adiabatic compressed air energy storage plant with combined sensible/latent thermal-energy storage are presented. The combined thermal-energy storage was composed of sensible and latent units with maximum capacities of 11.6 MWhth and 171.5 kWhth, respectively. The latent thermal-energy storage consisted of a steel tank with 296 stainless-steel tubes encapsulating an Al–Cu–Si alloy as phase-change material. The combined thermal-energy storage was investigated using four charging/discharging cycles with durations of about 3 h each and air inflow temperatures of up to 566 °C. The experimental results showed that the latent thermal-energy storage reduced the drop in the air outflow temperature during discharging. Minor leaks of the phase-change material were traced to the welding seams in the encapsulation as well as to holes required to insert resistance temperature detectors. Analysis of the leaked phase-change material revealed degradation and/or phase separation, which were attributed to the initial off-eutectic composition of and impurities in the phase-change material and resulted in a reduced heat of fusion. Simulations predicted the performance of the combined thermal-energy storage with good overall accuracy. Discrepancies were put down to changes in the thermophysical properties.